Alpha-melanocyte stimulating hormone inhibits monocytes adhesion to vascular endothelium. (November 2015) - Yang, Yang; Zhang, Weihua; Meng, Lin; Yu, Haitao; Lu, Na; Fu, Gang; Zheng, Yang
Inflammation and its subsequent endothelial dysfunction have been reported to play a pivotal role in the initiation and progression of chronic vascular diseases. Inhibiting the attachment of monocytes to endothelium is a potential therapeutic strategy for vascular diseases treatment. α-Melanocyte stimulating hormone is generated from a precursor hormone called proopiomelanocortin by post-translational processing. However, whether α-melanocyte stimulating hormone plays a role in regulating endothelial inflammation is still unknown. In this study, the effects of α-melanocyte stimulating hormone on endothelial inflammation in human umbilical vein endothelial cell lines were investigated. And the result indicated that α-melanocyte stimulating hormone inhibits the expression of endothelial adhesion molecules, including vascular adhesion molecule-1 and E-selectin, thereby attenuating the adhesion of THP-1 cells to the surface of endothelial cells. Mechanistically, α-melanocyte stimulating hormone was found to inhibit NF-κB transcriptional activity. Finally, we found that the effect of α-melanocyte stimulating hormone on endothelial inflammation is dependent on its receptor melanocortin receptor 1.